Cultura de tecidos de Euphorbia heterophylla L - Colussi, Francieli (2006)
The general objective of this research was the evaluation of in vitro culture of Euphorbia heterophylla L. one of the principal weeds that effects yield of important economic crops such as soybean and corn. In addition, some assays considered the evaluation of the species’ potential biochemical value to the pharmaceutical industry. In vitro germination of E. heterophylla seed was tested on cotton batting as substrate, full strength and ½ MS basal medium. Results show a greater percent germination and better growth indices of plant development on the ½ MS medium. Explants tested for organogenesis included hypocotyls, cotyledon and root explants which were plated on media containing the following plant growth regulators (phytohormones): 0.5 mg/L 2ip, 1mg/L Kin + 0.1 mg/L IAA, 0.5 mg/L 2ip + 0.1 mg/L IAA, 1mg/L 2ip + 0.1mg IAA, 1.5 mg.L-1 2iP + 0.1 mg.L-1 AIA added to ½ MS media. Explants were evaluated for the presence of buds, the number of buds/ explant and the number of plantlets that were rooted and re-established. On the average, hypocotyls explants responded with two buds/ explant and 50% of these developed by direct organogenesis on media containing 0.5 mg/L of 2ip. No regeneration was observed on cotyledon or root explants. Root cultures developed in all treatments with or without auxin. These results will assist in future physiological tests such as evaluating the herbicide resistance of this species and also in evaluating possible use in the pharmaceutical industry. With this objective in mind we tested the sensitivity of root cultures in vitro. Roots were placed in ½ MS media containing 0,1,2,4 and 8 times the manufacturer’s recommended dose for the products Scepter® and Flex®. The active ingredients were imazaquin and fomesafen respectively, and they are inhibitors of ALS synthesis and PROTOX. The results obtained showed evidence of suppression of the normal growth of these roots as compared to the control treatment. Therefore, this suggests that an in vitro test of this type can be used to measure resistance this species to herbicides.